Unveiling the middle ground: Intermediate-level linguistic differences and their influence on L2 writing proficiency - Guo, Lichao; Nik Aloesnita, Nik Mohd Alwi; Abdullah Adnan, Mohamed; Nguyen, Truong Sa (Academy Publication, 2025)
This study examines whether and how adult L2 learners' awareness of intermediate-level language difference (ILLD) affects their writing competence. Quantitative data were collected from 75 English-major university students using an explanatory sequential design, through questionnaires and IELTS Writing Task 2 tests. Correlation and error analyses revealed that understanding distinctions like the use of cohesive devices and substitution of words was linked to higher writing quality. Focus group interviews show that participants recognized the importance of these differences but often struggled to apply them in writing. Error analysis identified common issues, such as the lack of conjunctions and repetitive expressions. 3 of the 8 linguistic differences, including hypotactic versus hypotactic, impersonal versus personal and substitutive versus repetitive, had moderate correlations with writing competence, leading to frequent errors despite learners' theoretical knowledge. Less prominent differences, like indirect versus direct expression, showed weaker correlations and fewer errors. The study contributes both quantitative and qualitative evidence to a field previously dominated by surface-level analyses of CLI. Findings emphasize the need for guided practice in teaching ILLD. Targeted pedagogical interventions can enhance second language writing instruction, improving learners' accuracy, fluency, and overall communicative competence.